New Coupled Fixed-Point Results in Partially Ordered Metric Space for Contractive Mappings - Qazi Aftab Kabir, Mayanglambam Siddhartha, Ramakant Bhardwaj, Pankaj Kumar Mishra (International Journal of Advanced Science and Technology, 2020)
In this paper, we prove some new fixed-point theorems for contractive mappings in partially ordered metric space which generalize the common unique fixed-point theorem to the case of multivalued mappings in partially ordered metric space with closed bounded set. Our results are the extensions of the results of some well-known recent result in the literature. Example is given showing that our result is proper extensions of the existing ones.